A revisit to the structure of Au20(SCH2CH2Ph)16: a cubic nanocrystal-like gold kernel. Issue 22 (24th May 2018) - Wang, Pu; Sun, Xiangxiang; Liu, Xia; Xiong, Lin; Ma, Zhongyun; Wang, Yong; Pei, Yong
Abstract : A new stable structural form of Au20 (SR)16 cluster is theoretically predicted. The density functional theory (DFT) calculations with the inclusion of dispersion corrections indicated the nanocrystal-like isomer (Au20 -Iso1 ) has comparable and even lower total energies compared to the non-fcc crystal structure of Au20 (SPh- t Bu)16 . Abstract : Coinage metal clusters stabilized by organic ligands such as phosphine or organothiolate are well known to possess multi-twinned gold cores, and the face-centered-cubic (fcc) metal atom packing is unstable until the cluster size reaches a certain threshold. In this study, we searched for the smallest size gold nanocrystal protected by thiolate ligands by means of the crystal facet cleavage (CFC) method. Starting from the nanocrystal-like Au28 (SR)20 cluster, after cleaving two different crystal facets and patching the ligand shells, we obtained five nanocrystal-like Au20 (SR)16 isomers. These fcc-structured Au20 clusters were quite different from non-fcc Au20 (SPh- t Bu)16 ; the latter's total structure was determined by single X-ray diffraction. By employing dispersion correction density functional theory (DFT-D) calculations and considering ligand effects, we found that fcc-structured Au20 (SR)16 isomers had comparable or even lower energies when compared with the non-fcc structure found in Au20 (SPh- t Bu)16 . Furthermore, the calculation of optical absorption spectra based on predicted fcc isomers indicated that the cubic nanocrystal-like isomer structure is a good candidate to understand the structure of the Au20 (SCH2 CH2 Ph)16 cluster.